2022
DOI: 10.3389/fmicb.2022.819523
|View full text |Cite
|
Sign up to set email alerts
|

Marked Response of Rat Ileal and Colonic Microbiota After the Establishment of Alzheimer’s Disease Model With Bilateral Intraventricular Injection of Aβ (1-42)

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease. More evidence has shown that gut microbiota is closely associated with AD. Also, studies have shown that the distribution of gut microbiota vary in different sections of the intestine. In this study, a rat model of AD was established using a bilateral intraventricular injection of β-amyloid (1-42) [Aβ (1-42)], and the behavior of rats, hippocampal Aβ (1-42) deposition, and the ileal and colonic microbiota in each group were analyzed. We observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…These results suggested that Aβ 1–42 i.c.v can cause the alteration in the abundance of gut microbiota. In AD rat model caused by Aβ 1–42 i.c.v, Xu et al reported that Aβ injection could also cause the alteration in gut microflora at 4 weeks, which was consistent with our results [ 32 ]. In the analysis of gut microbiota abundance at the genus level, we found a decrease in the abundance of Alloprevotella , Ruminiclostridium , and Streptococcus , and an increase in the abundance of Akkermansia , Rikenella , and Adlercreutzia in the Aβ-treated group.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggested that Aβ 1–42 i.c.v can cause the alteration in the abundance of gut microbiota. In AD rat model caused by Aβ 1–42 i.c.v, Xu et al reported that Aβ injection could also cause the alteration in gut microflora at 4 weeks, which was consistent with our results [ 32 ]. In the analysis of gut microbiota abundance at the genus level, we found a decrease in the abundance of Alloprevotella , Ruminiclostridium , and Streptococcus , and an increase in the abundance of Akkermansia , Rikenella , and Adlercreutzia in the Aβ-treated group.…”
Section: Discussionsupporting
confidence: 93%
“…Each 25 μL reaction comprised 1X PCR buffer, 1.5 mM MgCl2, 0.4 μM dNTPs, 1.0 μM each of forward and reverse primers, 0.5 U TOYOBO KOD-Plus-Neo enzyme (Toyobo; Osaka, Japan; KOD-401B), and 10 ng of the template. The PCR program was set as follows: initial denaturation at 94 °C for 1 min; 30 cycles of denaturation at 94 °C for 20 s, annealing at 54 °C for 30 s, and extension at 72 °C for 30 s; and a final elongation step at 72 °C for 5 min [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…632 Interestingly, recent evidence has revealed the adverse effects of neuropathological changes in AD brains on the gut microbiome and intestinal barrier integrity. [633][634][635] A recently developed transgenic AD mice model with amyloid and neurofibrillary tangles pathology (ADLP APT mice) manifested altered gut microbiota, chronic intestinal inflammation, increased intestinal barrier permeability, and systemic inflammation. However, daily FMT from WT mice for 4 months successfully transformed the gut microbiota composition of ADLP APT mice, leading to restored circulating Ly6C hi monocytes population, reduced Aβ deposition, tau aggregates, and microglial activation.…”
Section: Points Of Intervention To Improve Microbiota-gut-brain Axismentioning
confidence: 99%